Combining Genes from Multiple Phages for Improved Cell Lysis and DNA Transfer from Escherichia coli to Bacillus subtilis. - Mario Juhas; Christine Wong; James W Ajioka (PLoS ONE)
The ability to efficiently and reliably transfer genetic circuits between the key synthetic biology chassis, such as Escherichia coli and Bacillus subtilis, constitutes one of the major hurdles of the rational genome engineering. Using lambda Red recombineering we integrated the thermosensitive lambda repressor and the lysis genes of several bacteriophages into the E. coli chromosome. The lysis of the engineered autolytic cells is inducible by a simple temperature shift. We improved the lysis efficiency by introducing different combinations of lysis genes from bacteriophages lambda, ΦX174 and MS2 under the control of the thermosensitive lambda repressor into the E. coli chromosome. We tested the engineered autolytic cells by transferring plasmid and bacterial artificial chromosome (BAC)-borne genetic circuits from E. coli to B. subtilis. Our engineered system combines benefits of the two main synthetic biology chassis, E. coli and B. subtilis, and allows reliable and efficient transfer of DNA edited in E. coli into B. subtilis.